2015
DOI: 10.1016/j.jmb.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for Maf1 beyond the Regulation of RNA Polymerase III Activity

Abstract: Maf1 was first identified in yeast and studies in metazoans have primarily focused on examining its role in the repression of RNA pol III-dependent transcription. Recent work has revealed a novel and conserved function for Maf1 in the maintenance of intracellular lipid pools in C. elegans, mice, and cancer cell lines. Although additional Maf1 targets are likely, they have not been identified, and these recent findings begin to define specific activities for Maf1 in multicellular organisms beyond the regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Maf1 inhibits tRNA transcription in S. cerevisiae , Drosophila , C. elegans , mice, and human cells under various stress conditions including calorie restriction (Khanna, Pradhan, & Curran, ). A recent report also showed that rapamycin decreases tRNA transcription in a Maf1‐dependent manner in S. pombe (Arimbasseri et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Maf1 inhibits tRNA transcription in S. cerevisiae , Drosophila , C. elegans , mice, and human cells under various stress conditions including calorie restriction (Khanna, Pradhan, & Curran, ). A recent report also showed that rapamycin decreases tRNA transcription in a Maf1‐dependent manner in S. pombe (Arimbasseri et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanism for MAF1 recruitment, in any organism, to chromatin is unknown, even more so for non-RNA pol III loci. Several models agree that MAF1 can interact with either RNA pol III itself or transcription factors to prevent transcription [5,6,10,11,16,17,24,27,28]. The expressions of pod-2/ACC1 and fasn-1/FASN are regulated by RNA pol II and SREBPs in C. elegans and mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In eukaryotes, RNA polymerase III transcribes tRNA genes, and this activity is regulated by different signaling pathways in response to growth factors, nutrient levels, mitogens, or stress (Dang 2012;Grewal 2015;Khanna et al 2015). Through protein kinase mTORC1, Maf 1 is a major repressor (Kantidakis et al 2010;Grewal 2015).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%